2012
DOI: 10.1111/j.1751-1097.2012.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase Activity and Acidic/Alkaline Balance as Factors Regulating the State of Phytochrome A and its Two Native Pools in the Plant Cell

Abstract: Phytochrome A (phyA), the most versatile plant phytochrome, exists in the two isoforms, phyA' and phyA'', differing by the character of its posttranslational modification, possibly, by phosphorylation at the N-terminal extension [Sineshchekov, V. (2010) J. Botany 2010, Article ID 358372]. This heterogeneity may explain the diverse modes of phyA action. We investigated possible roles of protein phosphatases activity and pH in regulation of the phyA pools' content in etiolated seedlings of maize and their extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…It was found that, in etiolated root tissues, NaF facilitated phyA′ destruction shifting the phyA′/phyA″ ratio towards phyA″ similarly to the effect of the specific inhibitors OA and CA in shoots, but with a lower extent, whereas in coleoptiles NaF was not active. This supports the notion [25] that the phosphorylation status of the cell regulates the phyA turnover in maize roots as well. However, the facts that NaF is active in roots, where the specific PP inhibitors, OA and CA, are inactive, whereas in stems the situation is reverse, suggest a different state of phyA and/or a different mechanism of action of the phyA destruction system in these organs.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…It was found that, in etiolated root tissues, NaF facilitated phyA′ destruction shifting the phyA′/phyA″ ratio towards phyA″ similarly to the effect of the specific inhibitors OA and CA in shoots, but with a lower extent, whereas in coleoptiles NaF was not active. This supports the notion [25] that the phosphorylation status of the cell regulates the phyA turnover in maize roots as well. However, the facts that NaF is active in roots, where the specific PP inhibitors, OA and CA, are inactive, whereas in stems the situation is reverse, suggest a different state of phyA and/or a different mechanism of action of the phyA destruction system in these organs.…”
Section: Introductionsupporting
confidence: 89%
“…Sodium fluoride (NaF) was used as a PP inhibitor with a wider range of the targets of its activity than the specific PP inhibitors (okadaic and cantharidic acids) previously employed in our experiments [25]. NaF is the source of the fluoride ions (F−) which irreversibly inhibit acidic serinethreonine phosphatases [28][29][30][31].…”
Section: Treatment With Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in Pr the chromophore adopts a ZZZssa conformation, Pfr is ZZEssa due to photoisomerization at the C15 = C16 double bond, although recent structural studies have shown that the A and particularly the D rings are twisted relative to the B-C ring plain (5)(6)(7)(8)(9)(10). Interestingly, however, Pr in various phytochromes is heterogeneous, the different substates being associated with spectroscopic, photochemical and/or structural differences (10)(11)(12)(13)(14)(15)(16)(17)(18). No such heterogeneity has been reported for Pfr, however.…”
Section: Introductionmentioning
confidence: 99%
“…Okadaic acid (OA) is a powerful inhibitor of protein serine/threonine phosphatases-1 and -2A (PP1 and PP2A) [ 23 ]. It is widely adopted that treating plants such as maize to study the effect of PP1 and PP2A activities on signal transmitting and gene activation [ 24 , 25 ]. In addition, OA has also been widely used to alter the state of histone phosphorylation in cell cycle progression and is a very good agent for investigating the relationship between chromatin modification and cell cycle progression [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%